IL-17, IL-27, and IL-33: A Novel Axis Linked to Immunological Dysfunction During Sepsis - Morrow, Kristen N.; Coopersmith, Craig M.; Ford, Mandy L. (Frontiers in Immunology, 2019)
Sepsis is a major cause of morbidity and mortality worldwide despite numerous attempts to identify effective therapeutics. While some sepsis deaths are attributable to tissue damage caused by inflammation, most mortality is the result of prolonged immunosuppression. Ex vivo, immunosuppression during sepsis is evidenced by a sharp decrease in the production of pro-inflammatory cytokines by T cells and other leukocytes and increased lymphocyte apoptosis. This allows suppressive cytokines to exert a greater inhibitory effect on lymphocytes upon antigen exposure. While some pre-clinical and clinical trials have demonstrated utility in targeting cytokines that promote lymphocyte survival, this has not led to the approval of any therapies for clinical use. As cytokines with a more global impact on the immune system are also altered by sepsis, they represent novel and potentially valuable therapeutic targets. Recent evidence links interleukin (IL)-17, IL-27, and IL-33 to alterations in the immune response during sepsis using patient serum and murine models of peritonitis and pneumonia. Elevated levels of IL-17 and IL-27 are found in the serum of pediatric and adult septic patients early after sepsis onset and have been proposed as diagnostic biomarkers. In contrast, IL-33 levels increase in patient serum during the immunosuppressive stage of sepsis and remain high for more than five months after recovery. All three cytokines contribute to immunological dysfunction during sepsis by disrupting the balance between type 1, 2 and 17 immune responses. This review will describe how IL-17, IL-27, and IL-33 exert these effects during sepsis and their potential as therapeutic targets.